Exploring Key Factors Influencing Digital Payment Continuance: Digital Financial Literacy, Security Behavior and UTAUT - Ananta, Dinda Dwi; Juita, Verni (Jurnal Eksplorasi Akuntansi, 2026)
The rapid growth of digital payment adoption has been accompanied by increasing concerns over transaction security risks, which can lead to both financial and non-financial losses for users. Addressing this issue, the present study investigates the determinants of continuance intention in digital payment usage, emphasizing the roles of digital financial literacy (DFL), online security behaviour (OSB), and the constructs from the Unified Theory of Acceptance and Use of Technology (UTAUT). Using a quantitative research design, data were collected from 449 digital payment users using snowball sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that online security behaviour, performance expectancy, social influence, and facilitating conditions have a significant positive effect on users’ intention to continue using digital payment services. These findings highlight the importance of user capabilities and perceptions in ensuring the sustainable adoption of digital financial services.